Humor in Dark Personalities: An Empirical Study on the Link Between Four Humor Styles and the Distinct Subfactors of Psychopathy and Narcissism - Lobbestael, Jill; Freund, Vanessa Lea (Frontiers in Psychology, 2021)
Background: Humor is a main ingredient of interpersonal relationships. Two sets of psychopathologic traits known for their devastating impact on interpersonal relationships are psychopathy and narcissism. The current study was developed to provide a fine-grained analysis of the relationship between four humor styles (affiliative, self-enhancing, self-defeating, and aggressive) and both psychopathic and narcissistic traits. Specifically, it addresses how humor styles relate to the three psychopathy subfactors (following the triarchic model) and four subfactors of grandiose narcissism. Method: Self-report measures in a non-clinical male sample N=177. Results: Multiple regression analyses revealed psychopathic and narcissistic traits` relation to using both benign and injurious humor. Subfactor analyses showed that aggressive and self-defeating humor were mostly associated with impulsivity and entitlement, while dominance levels actuated the use of humor to cope with stress. The Cold-heartedness component of psychopathy proved to be particularly humor-less, setting it aside as a distinctively disturbing psychopathic subfactor. Conclusions and implications: Humor strongly colors the interpersonal style of both psychopathic and narcissistic personalities. Differential components of both personality types inform on the possible underlying motivations that drive the use of distinct styles of humor. This implies that psychopathic and narcissistic traits could potentially be lowered through the alternation of humor styles.